KECERDASAN EMOSIONAL DAN DAMPAKNYA TERHADAP STRES KERJA DAN KINERJA KARYAWAN - MUHAMMAD RASYID ABDILLAH; ADI RAHMAT (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". The studies that prove and explain the mediation role of job stress in the influence of emotional intelligence on the performance of individuals has still limited, especially in private companies. The purpose of this study to examine empirical evidence that job stress mediate the effect of emotional intelligence on employee performance. The data used in this study was primary data in the form of a questionnaire in which the research subjects are 53 employees of PT. Adei Plantation & Industry Head Office Pekanbaru Riau. To test the hypothesis using Structural Equation Modeling Partial Least Square. The result of this study concluded that the effect of emotional intelligence on employee performance is indirect influence through job stress. In addition, result also concluded that job stress is a variable that full mediates the influence of emotional intelligence on employee performance.